The structure of RUB-1, (C8H16N)6[B6Si48O108], a boron containing levyne-type zeolite, occluding N-methyl-quinuclidinium in the cage-like pores - Gruenewald-Lueke Antje; Grosskreuz Isabel; Gies Hermann; Marler Bernd (Zeitschrift für Kristallographie - New Crystal Structures)
C48H96B6N6O108Si48, trigonal, R3‾m$R\overline{3}m$ (no. 166), a = 12.8892(1) Å, c = 22.3058(2) Å, V = 3209.23(4) Å3, Z = 1, density = 2.02(2) g·cm−3, R(F) = 0.038, Chi2 = 2.86, T = 293 K.